Effect of Different Stabilizer Addition on Preparation and Hydrothermal Stability of ZrO2-TiN Composites with Varying TiN Content - Arin, Melis; Vleugels, Jef; Vanmeensel, Kim; Göller, G. (Trans Tech Publications Ltd., 2007)
Fully dense ZrO2-TiN composites containing 1.75-2 mol %Y2O3, 1 mol% Y2O3 and 1 mol% Nd2O3 stabilizers, small amounts of Al2O3, and electrical conductive TiN particles (40-70 vol%) have been produced by hot pressing and spark plasma sintering at 1550°C. Although the intrinsic hardness of TiN (1400 kg/mm²) is higher than that of t-ZrO2 (1200 kg/mm²), the decreasing hardness trend can be attributed to the larger TiN grain size with the higher TiN content. Since TiN is more brittle, the fracture toughness decreases with increasing TiN content. Transformation toughening has been attributed as the main toughening mechanism as a result of fracture toughness decreasing with the transformability. Spark Plasma sintering temperature was too high for mechanical properties and hydrothermal stability of the mixed stabilized composites. The transformability decreases so hydrothermal stability increases linearly with increasing TiN content as a result of smaller volume fraction of t-ZrO2 grains becoming susceptible to hydrothermal transformation due to the shielding effect of the present TiN grains.